Positioning of large organelles by a membrane-associated cytoskeleton in Plasmodium sporozoites - Kudryashev, Mikhail; Lepper, Simone; Stanway, Rebecca; Bohn, Stefan; Baumeister, Wolfgang; Cyrklaff, Marek; Frischknecht, Friedrich (Cellular microbiology, 2010)
Cellular organelles are usually linked to the cytoskeleton, which often provides a scaffold for organelle function. In malaria parasites, no link between the cytoskeleton and the major organelles is known. Here we show that during fast, stop-and-go motion of Plasmodium sporozoites, all organelles stay largely fixed in respect to the moving parasite. Cryogenic electron tomography reveals that the nucleus, mitochondrion, apicoplast and the microtubules of Plasmodium sporozoites are linked to the parasite pellicle via long tethering proteins. These tethers originate from the inner membrane complex and are arranged in a periodic fashion following a 32 nm repeat. The tethers pass through a subpellicular structure that encompasses the entire parasite, probably as a network of membrane-associated filaments. While the spatial organization of the large parasite organelles appears dependent on their linkage to the cortex, the specialized secretory vesicles are mostly not linked to microtubules or other cellular structures that could provide support for movement.
Gesehen am 07.03.2023